Foreign Nation Visibility in U.S. News Coverage: A Longitudinal Analysis (1950-2006). (June 2013) - Jones, Timothy M.; Van Aelst, Peter; Vliegenthart, Rens
Previous scholarship has neglected to fully explore the dynamic nature of international news flow over time. This study uses content analysis to track foreign nation visibility on a yearly basis in two major U.S. news outlets: the New York Times (1950-2006) and NBC Nightly News (1968-2006). Time-series analysis is used to evaluate the influence of five contextual factors on foreign nation visibility in the news: (a) geographic proximity, (b) bilateral trade flow, (c) U.S. troop deployment, (d) GDP per capita, and (e) population. The research findings build on earlier news flow studies by adding a longitudinal dimension that has been absent from previous news "flow" scholarship.